Analysis of the data obtained while studying European plum (Prunus domestica L.) cultivars developed at Maikop Experiment Station of VIR - V. V. Sherstobitov; I. A. Bandurko; P. V. Ozerski (Труды по прикладной ботанике, генетике и селекции)
Background. European plum (Prunus domestica L.) is one of the leading stone fruit crops cultivated in Southern Russia. Therefore, it is very important to study the adaptability of its cultivars comprehensively.Materials and methods. European plum cultivars with different maturation periods developed at Maikop Experiment Station of VIR were studied in 2008–2021 under the conditions of the field gene bank of Maikop Experiment Station. The calendar dates were recorded for the passage of the important phenological phases. Productivity, commercial and consumer fruit qualities, and fruit weight were assessed using conventional techniques.Results. The growing season of the studied plum cultivars started from March 15 (‘Vengerka Maikopskaya’, k-15081) to April 16 (‘Spurochka’, k-43477). The beginning of flowering was recorded from April 9 (‘Vengerka Maikopskaya’) to April 22 (‘Vengerka Tsitvenbyul’, k-43331). The flowering phase duration was 7 to 10 days. The flowering phase started later for cvs. ‘Vengerka Maikopchanka’ (k-43326), ‘Vengerka Sladkaya’ (k-43329), ‘Vengerka Tsitvenbyul’, ‘Vengerka Shuntuchka’ (k-43334) and ‘Lakomka’ (k-43471). Mass fruit ripening was observed from August 5 to September 9. The highest fruit flavor score was recorded for cvs. ‘Arvita 44-4-10’ (k-28409), ‘Vengerka Vkusnaya’ (k-43323), ‘Vengerka Sladkaya’, ‘Vengerka MOS VIR’ (k-15080), ‘Vengerka Shuntukskaya’ (k-15079), ‘Izmamot’ (k-48408) and ‘Chernosliv Adygeiskiy’ (k-23743). Large-fruited cultivars were: ‘Chernosliv Adygeiskiy’, ‘Chernosliv Predgorny’ (k-43488), ‘Arvita 44-4-10’, ‘Vengerka Vkusnaya’, ‘Vengerka MOS VIR’ and ‘Vengerka Maikopskaya’. Higher productivity was observed in cvs. ‘Vengerka Sladkaya’, ‘Chernosliv Adygeiskiy’ and ‘Chernosliv Shuntukskiy’ (k-23707). Cultivars with the most stable productivity were ‘Arvita 44-4-10’, ‘Vengerka Sladkaya’ and ‘Chernosliv Adygeiskiy’.Conclusions. Analyzing the results of a long-term study of plum accessions helped to identify cultivars with the most valuable traits.